Governance and Resilience: Unpacking Policy Decisions in Mamuju’s Earthquake Aftermath - Syam, Abdul Rahman; Putra, Muhammad Aidil; Muslim, Aziz (Departemen Ilmu Administrasi FISIP UNHAS, 2024)
The study is aimed at knowing government decisions to make post-earthquake recovery in the city of Mamuju, where decisions have become binding policies and have become basic concepts in the restoration practice of the Mamuju city. The method used is researchers is descriptive research using a qualitative approach. The approach to this study is a narrative description because it is directed to illustrate the facts with scientific & academic arguments. The results of the provincial government's policy research in the reconstruction of the city's Mamuju following the earthquake's efforts, such as the allocation of the public budget (APBD), the structural improvements of the office building with bracing and jacketing concepts, provide financial assistance to disaster affected communities, the formation of working groups (POKJA), and finally the reconstruction of the affected areas. Policies adopted by governments have been carefully thought out by stakeholders to accelerate recovery. The government issued swift and precise decisions, as they were pushed by the circumstances and conditions following the earthquake hit the city of Mamuju. The policies issued by the government are well considered. Because the essence of the policy itself is the decisions governments make to simply achieve a common goal.